Description of Lip Print Patterns (Cheiloscopy) Based on Age in the Population of Bojonegoro, East Java, Indonesia - Mahriana Mahriana; Dwi Kartika Apriyono; Masniari Novita (Humanistic Network for Science and Technology (HNST), 2023)
Forensic dentistry is a branch of medical science that deals with identifying and examining evidence through teeth and evaluating and presenting findings related to the oral cavity, jaws, teeth, and oral soft tissues to determine a person's identity. One of the identification methods that can be used in forensic odontology is lip prints. This study aims to see and examine the appearance of lip print patterns (cheiloscopy) based on age in Bojonegoro, East Java, Indonesia. This research was a descriptive observational study with a cross-sectional approach and used the classification of lip print patterns proposed by Suzuki & Tsuchihashi. The research sample consisted of 100 people taken from the age group of toddlers, children, adolescents, early adults, late adults, early elderly, late elderly, and seniors. The results of this study indicated that the most common lip print pattern was type II followed by type III and type I. There was diversity and variation in lip print patterns in each age group in Bojonegoro, East Java, Indonesia. Possibly due to racial variations and subject maturity. Keywords: forensic identification; lip print; cheiloscopy